A review on optimization of energy efficiency in buildings: Smart cities - DHARSHINI G M, AKSHAYAKUMAR V H (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The massive development of developing countries increases the energy consumption continuously.Energy savings and reduction of emission are the main goals of construction industry. The main objectives to improve the productions of energy and reduction of energy consumption and cost. The consumption of energy in buildings results in direct and indirect impacts over the lifespan of the building which leads to global warming, carbon footprint and indoor air pollution etc. The paper mainly focuses on reduction of energy consumption in buildings as well as all the methods have been discussed to reduce energy. The metamodel-based optimization, simulation algorithms, artificial neural network models, supervised data mining -based methods,Deep neural networks,Sampling method,BIM-LCA integration, data driven methods,clustering based methods, have been discussed to save consumption of energy in buildings.